A MULTIMODAL ANALYSIS OF MATHEMATICAL DISCOURSE IN ENGLISH FOR YOUNG LEARNERS - Nhat, Ton Nu My (VNU Journal of Foreign Studies; Vol 33 No 6, 2017)
Of multiple discourses where the Vietnamese young learners are increasingly engaged to develop their English profciency, English mathematical discourse (MD) has proved to be more and more popular. This paper explores the materials in this realm from multisemiotic perspective. In particular, it deals with two questions: (1) to what extent each of the three semiotic resources - language, visual images and mathematical symbolism - is represented in the materials of learning mathematics in English (ME) developed for young learners (YL) and (2) how many words the YLs need to know to comprehend the language component of these materials. Data for illustrations and discussions are withdrawn from the printed resources currently accessible in the Vietnamese context. The results offer insights into the functions of other resources in constructing meanings apart from the well-established role of language as well as the vocabulary load of these materials. The paper concludes with a discussion of pedagogical signifcance of this study for material designers, teachers and learners and implications for further research.